Sustainable Human Resource Management (HRM) Development in Higher Education Environments - Nuryadi; Achmad Nur Amin; Abdul Rahman (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The development of sustainable Human Resource Management (HRM) is a strategic aspect in enhancing the quality and competitiveness of higher education institutions. Universities are required to manage human resources in a professional, adaptive, and long-term-oriented manner in order to respond to technological advancements, labor market demands, and changes in the higher education system. Higher education institutions, particularly those in the fields of economics and business, need to implement sustainable HRM practices to create human resources that are competent, productive, and committed to institutional development. This article aims to examine the concept of sustainable HRM development, formulate applicable human resource development strategies, and provide policy recommendations for HRM management in higher education institutions. The method used in this study is a qualitative descriptive approach through a literature review and conceptual analysis of HRM management practices in higher education institutions. The results of the discussion indicate that sustainable HRM development can be achieved through improving the competencies of lecturers and educational staff, implementing objective performance appraisal systems, developing transparent career paths, and utilizing digital technology in human resource management. The implementation of sustainable HRM in higher education institutions is expected to enhance the performance of the academic community, improve the quality of educational services, and support the sustainable achievement of the institution’s vision and mission. Keywords: human resource management, sustainable HRM, higher education, higher education institutions